Personalities of the Polish world of music and theater at the turn of the 19th and 20th centuries in the caricature of Eli Kochański - Fink, Kinga (Laughter, humour, satire, 2024)
Eli Kochański (1885–1940), a musician now forgotten, was one of the famous figure of interwar Warsaw. He was an excellent cellist, concertmaster of the Warsaw Philharmonic Orchestra and professor at the State Conservatory of Music in Warsaw. He also became famous as the author of a series of caricatures depicting personalities of the world of music at time and from the circle of the Warsaw music community. His drawings were published in music magazines („Wiadomości Muzyczne”, „Muzyka”), cultural and social magazines („Tygodnik Ilustrowany”) and daily newspapers („Kurier Warszawski”, „Dziennik Poznański”) in the years 1925–1936 and caused a lively resonance among the inhabitants of the capital.This article will discuss selected caricatures by Kochański published in interwar magazines and from the collections of the National and Jagiellonian libraries. Among them are e.g. humorous portraits of Bronisław Huberman, Paweł Kochański, Ignacy Jan Paderewski, Mieczysław Frenkiel. The iconographic sources has been submitted to analyses, focusing above all on deciphering the author’s intentions and allusions to current events in the artistic life of Warsaw in the first thirty years of the 20th century.